Revision of the genus Ortopla Walker, [1859] with description of two new species from Southeast Asia (Lepidoptera, Noctuidae, Pantheinae). Revision of Pantheinae, contribution X - Behounek, G.; Han, H. L.; Kononenko, V. S. (Zootaxa, 2013)
The pantheine genus Ortopla Walker, [1859] 1858 is revised. Two new species, Ortopla witti sp. n. from the Philippines and O. longiuncus sp. n. from Nepal, Vietnam, Thailand, Myanmar and South China are described. The name O. commutanda Warren, 1891 (syn. n.) is synonymised with O. iarbasalis Walker, [1859] 1858. The distribution of species in East Asia is clarified. A checklist of the genus Ortopla is presented. Imagines, male and female genitalia of all species are illustrated.